SADISTIC PERSONALITY DISORDER PORTRAYED BY PATRICK BATEMAN IN AMERICAN PSYCHO FILM - Rini, Maria F; Separ, Fransiskus M; Liru, Marianus W (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2023)
People with sadistic personalities or mental disorders can be seen from their attitude and behavior. The sadistic nature depicted in a person's life is his bad behavior. The descriptive method of analysis was carried out by describing the sadistic personality disorder played by Patrick Bateman in the American psycho film, namely the characters and the causes of sadistic personality disorder that are described by the main character. The author uses a qualitative descriptive method, to describe a person's behavior and actions as data in analyzing the problem formulation. This study aims to find the sadistic personality disorder described by Patrick Bateman including the characters and triggering factors in the American Psycho film. Data is taken in the form of phrases, sentences and paragraphs. The approach used by the author is a psychological approach that is concerned with sadistic personality disorder. The research results show that there are three types of characters, namely the mad scientists, the schemer of court, and the trickster. The second is the causative factor, namely the biological mechanism and socioeconomic status that shows behavior, acts of violence, sexual. As well as repeated killing